SELF PRESENTATION ANGGOTA KOMUNITAS MOTOR RX-KING MRC (KAJIAN DRAMATURGI TENTANG PRESENTASI DIRI ANGGOTA KOMUNITAS MOTOR RX-KING DI KOTA SALATIGA) - Muhammad Bariqi Najman; Nurul Hasfi (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2019)
The RX-King motorcycle community is one of hundreds of well-known motorcycle communities in Indonesia. This community is seen as a frightening community because of the image of the RX-King itself which is famous as the